A retrospective audit of young adults who received permanent pacemakers at a teaching hospital in the Western Cape, South Africa - Hugo, Elrike; Doubell, Anton; Steyn, Jan; Moses, Jane (Frontiers in Cardiovascular Medicine, 2023)
While most pacemaker implantations occur in older individuals, younger patients also receive pacemakers. In these, degenerative conduction system disease is less likely to be the cause of atrioventricular block (AVB), with other diseases being more common. There is, however, a paucity of data on this group as well as on younger pacemaker recipients that have undergone pacemaker implantation for reasons other than AVB. The aim of this study was to perform an audit of young adult permanent pacemaker recipients. This was a retrospective record review, conducted in the Division of Cardiology at Tygerberg Hospital, Cape Town, South Africa. We included 169 adult patients between the ages of 18 and 60, who received permanent pacemakers between 2010 and 2020. A subgroup analysis of patients 55 years and younger was also performed. Third degree AVB was the most common indication for pacemaker implantation (n=115;68%), followed by high degree AVB (n=23;13.6%) and sick sinus syndrome (SSS; n=14;8.3%). A specific underlying cause for conduction system abnormalities was found in only 25.4% of patients (n=43), with most of them being 55 years or younger (n=32;30.8 % of patients < 55 years). Specific causes that were identified included prosthetic valve implantation and/or valve repair (n=14;8.3%), myocardial infarction (n=6;3.6%), cardiac sarcoidosis (n=5;3.0%), coronary artery bypass grafting (n=3;1.8%), cardiomyopathy (n=2;1.2%), muscular dystrophy (n=2;1.2%), congenital heart disease (ventricular septal defect; atrioventricular septal defect; Tetralogy of Fallot; bicuspid aortic valve; n=6;3.6%), acute myocarditis (n=1;0.6%), atrial myxoma removal (n=1;0.6%), planned AV node ablation (n=2;1.2%), and following a previous stab in the chest (n=1;0.6%).Given that the mean age of our study population was high, the low number of identified underlying causes in the whole cohort (<60 years) may reflect some AVB due to age related degeneration of the conductions system in the patients 56 to 60 years age, but also raises the possibility that these patients may be less likely to be extensively investigated for an underlying cause than those < 55 years, where diseases such as sarcoidosis were more readily confirmed. As access to advanced diagnostic tools improves, the percentage of young pacemaker recipients with an underlying cause identified may increase.